"THE STUDY OF PRIMITIVE MUSICAL INSTRUMENTS. Brief notes on some existing approaches and systems of classification”, by David Rycroft, Review of Ethnology, Volume 1, 1969, No. 14, pp. 1-8, and No. 15, pp. 1-5, Institut fur Volkerkunde, Vienna University - Tracey, Hugh (International Library of African Music, 1970)
pages: 126
Keywords: African Music